2019
DOI: 10.5937/ffr1901037p
|View full text |Cite
|
Sign up to set email alerts
|

Histamine levels in fish samples collected from Serbian market in 2018

Abstract: Histamine is a biogen amin, which is formed by decarboxylation of the histidine amino acid, under the action of the L-histidine-decarboxylase enzyme. High level of free histidine in fish meat, bacterial histidin decarboxylase activity and high temperature of storage elevate the level of histamine. Among the most important factors that can affect the level of histamine in fish meat are the type of fish and the method of its preservation. In order to determine this dependence, 1030 samples of frozen fish (tuna, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In literature high levels of histamine in frozen nonscombroid fish species have been also reported by other authors (Auerswald et al, 2006); (Mejrhit et al, 2018). Similar studies have showed a high level of histamine in frozen non scombroid fish type (Pavloc et al, 2019). The variation of histamine level in frozen samples can be caused by the period of heat where wholesales may not control the storage temperature of samples.…”
Section: Histamine Level In Frozen Fishsupporting
confidence: 64%
See 1 more Smart Citation
“…In literature high levels of histamine in frozen nonscombroid fish species have been also reported by other authors (Auerswald et al, 2006); (Mejrhit et al, 2018). Similar studies have showed a high level of histamine in frozen non scombroid fish type (Pavloc et al, 2019). The variation of histamine level in frozen samples can be caused by the period of heat where wholesales may not control the storage temperature of samples.…”
Section: Histamine Level In Frozen Fishsupporting
confidence: 64%
“…Low limit of histamine in scombroid samples were found with other authors (Gonzaga et al, 2009;Pavloc et al, 2019;Marilena et al, 2013;Feng et al, 2015). Fish are more likely to decompose and form toxic by fish products when decomposition occurs at harvest or in the first stages of handling on fishing vessels, rather than later in the distribution chain, according to FDA experience with the preparation of standard packs of fish and the examination of many samples of seafood implicated in human poisonings (Staruszkiewicz et al, 2004).…”
Section: Histamine Level In Frozen Fishmentioning
confidence: 67%